Designing Waste Water Treatment Unit for Methanol Plant - Nur Shafinaz Bt Shafee, Nur Shafinaz (Universiti Teknologi Petronas, 2009)
Water Treatment System is specially designed to treat the water or effluent before being discharged into the sea water, river or other water sources. Usually it is installed because the effluent contains lots of chemicals, suspended solids or micro organisms. These will definitely contribute to the water pollution. This should be avoided because the pollution will affect the human health and the main is the environment itself. Different industry will have to use different technologies of water treatment depending on the chemicals or materials used. The water treatment technologies are activated sludge systems, sand filter, aerated lagoon, bead filter, ion exchange and dissolved air flotation. Certain area of study needs to be revised to produce a water treatment unit that is useful in reducing the certain parameters such as BOD (Biological Oxygen Demand), COD (Chemical Oxygen Demand) and Cadmium ion. From the analysis done, BOD is obviously the critical parameter where it should be treated before being discharge. The suitable treatment is the biological wastewater treatment. Activated sludge process is the type of biological wastewater treatment to be used. Using this treatment, BOD can be reduced up to 95 – 98%. However, since there some other heavy metals exceed too, the treatment should be started with pre-treatment first to remove them because heavy metals will cause toxicity during the activated sludge process.